KARAKTERISTIK FUNGSIONAL TELUR INFERTIL SISA HASIL PENETASAN YANG DIFERMENTASI MENGGUNAKAN Saccharomyces cerevisiae PADA LEVEL YANG BERBEDA (Functional Characteristics of Egg Infertile Hatchery Remaining at Fermentation in Saccharomyces cerevisiae Using Different Level) - L. Amaliah; Nahariah Nahariah; H. Fattah; H. M. Ali (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2017)
Infertile eggs obtained from hatchery process has experienced a declined characteristic in the functional properties. The decrease is due to the storage and warming up during the hatching process. An attempt should be taken to improve it through a fermentation process. This study aimed to determine the functional characteristics of infertile egg which was fermented using different levels of Saccharomyces cerevisiae. This study was carried out according to completely randomized design (CRD) with 4 treatments and 3 replications. The parameters measured were the power of foam, foam stability, coagulation time and gel strength. The results showed that the fermentation of infertile eggs using different levels of Saccharomyces cerevisiae signifcantly (P<0.05) affected the foam power and foam stability and became highly signifcant (P<0.01) against coagulation time, but had no effects (P>0.05) on the gel strength. Fermentation using Saccharomyces cerevisiae at the level of 6% can maintain gel strength, improving foam, foam stability and coagulation time of infertile eggs obtained from the hatching process.